1970
DOI: 10.32413/pjph.v6i4.13
|View full text |Cite
|
Sign up to set email alerts
|

An Epidemiological Analysis of Socioeconomic Risk Factors Among Patients of Rheumatic Heart Disease, Islamabad, Pakistan

Abstract: BACKGROUND: Rheumatic Heart Disease (RHD) is a disease of developing countries where it inflects significant burden dis-proportionality. We investigated the role of socio-economic and environmental risk factors for RHD. METHODS:· This was descriptive cross-sectional conducted at Pakistan Institute of Medical Sciences Islamabad by including the patients coming to cardiology out door patient department through convenient sampling technique. Study was approved from ethical committee of Pakistan institute of Med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Detailed clinical characteristics and manifestation are presented in Table 1. Severity of MS was very severe in 8.8% (11), severe in 74.4% (93), and progressive in remaining 16.8% (21). On TTE left atrial thrombus was seen in 8% (10), left atrial smoke in 9.6% (12), and vegetation were seen in 3.2% (4) of the patients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Detailed clinical characteristics and manifestation are presented in Table 1. Severity of MS was very severe in 8.8% (11), severe in 74.4% (93), and progressive in remaining 16.8% (21). On TTE left atrial thrombus was seen in 8% (10), left atrial smoke in 9.6% (12), and vegetation were seen in 3.2% (4) of the patients.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, various studies reported varying rate of RHD in our population depending on region and social segment under study. [10][11][12] The management recommendations as well as timing of management are mostly dependent on individual risk profile of patient, anatomical factors of mitral valve, functional status of the patients, associated valve pathology, and surgical risk of individual, hence all come to play when deciding management strategy. 13,14 In our study only 19.2% of the patients were managed medically, while remaining patients required either surgical or interventional management.…”
Section: Discussionmentioning
confidence: 99%
“…Rheumatic fever is commonly seen in underdeveloped countries and also shows a high prevalence in Pakistan. 1 , There has been a trend in the increase of rheumatic cases in our region especially of mitral stenosis from the past 40 years 2,3 Mitral stenosis has been considered as one of the commonest valvular pathology associated with it and, if not treated timely leads to different complications 4,5 and resultantly high morbidity and mortality. 6 Various treatment options are available including medical management, balloon commissurotomy and finally surgical replacement of the diseased valve with prosthetic one.…”
Section: Introductionmentioning
confidence: 99%